Design and Implementation of a Node.js Based Computer Network Monitoring Information System at the Department of Communication and Information of Kebumen Regency - Taufiqurrokhman, Imam; Sufyana, Candra Mecca (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2021)
Large and complex computer networks have a high risk of failure, so they require monitoring and mapping to maintain service availability. An information system must monitor and map computer networks so that supervision is not done manually and problem handlings can be done quicker. This study aims to design and implement a computer network monitoring-information system at the Department of Communication and Informatics of Kebumen Regency by utilizing the waterfall software development method. UML modelling language used in the design of computer network monitoring information system and implemented with the JavaScript programming language on Node.js runtime environment. This system utilizes the interval function in JavaScript and the system utility from Node.js to check the network devices. This system sends notifications of the network client status changes to registered users. Based on the test results, this system can monitor and provide notifications as well as a map of the computer network belonging to the Kebumen Regional Government, which is managed by the Department of Communication and Information Technology of Kebumen so that the process of handling computer network problems belonging to the Kebumen Regional Government can be carried out more optimally.